MANAJEMEN KOMUNIKASI PENDIDIKAN ISLAM - Iiyang Putri; Muhammad Al Faruq; Mohammad Khamami Zadih; Kalimatun Naimah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2024)
Humans are social creatures, in order to have good social relations, humans have a communication process with other humans, everyone has the right to communicate in accordance with the 1945 Constitution, article 28 F. In reality, the communication process is not always smooth, this happens because of a lack of attention to existing elements. in communication. In the world of education, communication is very important because every day you are required to communicate with other people who are involved in the same world. There are six components of the principles of communication explained in the Al-Qur'an, the aim is to create an understanding between educators and students. Communication management is basically is a combination of communication science and management theory applied in many different communication contexts. Communication management can also be understood as the systematic planning, implementation, monitoring, and review of all communication channels within a company or organization and also between organizations including organizing and disseminating guidelines for new communications connected to a network, organization, or communication technology. Keywords: Communication management